2014
DOI: 10.3171/2014.3.focus1426
|View full text |Cite
|
Sign up to set email alerts
|

Clinical improvement through nonoperative treatment of adult spinal deformity: who is likely to benefit?

Abstract: Object The goal of this study was to determine the outcome and risk factors in patients with adult spinal deformity (ASD) who elected to receive nonoperative care. Methods In this retrospective study the authors reviewed a nonoperative branch of the International Spine Study Group database, derived from 10 sites across the US. Specific inclusion criteria included nonoperative treatment for ASD and the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…6,41 The International Spine Study Group reported that patients who were treated nonoperatively for adult spinal deformity gained an average 0.27 MCID by the 1-year follow-up visit; of the patients who experienced significant improvement (defined as > 1 MCID), a 24% reduction in pain was revealed. 40 Thus, it was concluded that nonoperative treatment is a viable option for certain patients with adult spinal deformity of the mildest degree for whom surgery can be avoided; in contrast, patients with the worst baseline scores might be advised to proceed directly to surgery and avoid the unnecessary costs and prolonged discomfort of a futile nonoperative trial. 40 With respect to the outcome of limited surgery, a previous report indicated that the interbody fusion of short segments is ineffective at restoring sagittal balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,41 The International Spine Study Group reported that patients who were treated nonoperatively for adult spinal deformity gained an average 0.27 MCID by the 1-year follow-up visit; of the patients who experienced significant improvement (defined as > 1 MCID), a 24% reduction in pain was revealed. 40 Thus, it was concluded that nonoperative treatment is a viable option for certain patients with adult spinal deformity of the mildest degree for whom surgery can be avoided; in contrast, patients with the worst baseline scores might be advised to proceed directly to surgery and avoid the unnecessary costs and prolonged discomfort of a futile nonoperative trial. 40 With respect to the outcome of limited surgery, a previous report indicated that the interbody fusion of short segments is ineffective at restoring sagittal balance.…”
Section: Discussionmentioning
confidence: 99%
“…40 Thus, it was concluded that nonoperative treatment is a viable option for certain patients with adult spinal deformity of the mildest degree for whom surgery can be avoided; in contrast, patients with the worst baseline scores might be advised to proceed directly to surgery and avoid the unnecessary costs and prolonged discomfort of a futile nonoperative trial. 40 With respect to the outcome of limited surgery, a previous report indicated that the interbody fusion of short segments is ineffective at restoring sagittal balance. In patients with PDSI, alternative surgical techniques, such as corrective osteotomy, should be considered before performing limited surgery.…”
Section: Discussionmentioning
confidence: 99%
“…3, 24 , 3 Slobodyanyuk et al showed only 24% of patients treated nonoperatively had clinical improvement at 1 year. 4…”
Section: Discussionmentioning
confidence: 99%
“…2 Previous studies have suggested that nonoperative modalities are not effective in improving Patient Reported Outcomes (PROs) in Adult Symptomatic Lumbar Scoliosis (ASLS). 3, 4…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, epidural steroid injections (ESIs) have been used as a conservative method to control spinal pain. ESIs can be performed via an interlaminar, transforaminal, or caudal route (21).…”
mentioning
confidence: 99%